Analisis Kepercayaan dan Kepuasan terhadap Loyalitas Pelanggan Honda Motor - Andi Yulianto; Budi Raharjo (Program Studi Manajemen Universitas Muhadi Setiabudi, 2021)
In the industrial world, customer loyalty is a measure of success in the manufacturing and sales industry. Customers will feel much more satisfied if the company can meet customer needs far beyond what is expected. Likewis with HONDA MOTOR, which emphasizes the evaluation of successful trust, and satisfaction through customer opinions filled by HONDA MOTOR customers. The loyalty of customers who are trying to achieve by HONDA MOTOR can be measured by distributing questionnaires to be filled out by customers. The sample in this study were 255 customers or HONDA MOTOR users. The questions in this questionnaire are closely related to employee promotions, employee service quality, customer trust, and customer satisfaction from the perspective of the perception of customer loyalty. The results of the answers to this questionnaire will be calculated to determine how much influence it has on customer loyalty. By knowing the results of this study related to customer loyalty, HONDA MOTOR can understand more deeply about customer views on promotion, service quality, trust and satisfaction and to determine the right strategy to improve performance in the future in order to achieve customer loyalty